Task-Level Mapping of Electrical and Oil-Handling Risks during Transformer Oil Purification: A Job Safety Analysis at PT PLN Batam - Nanda Putri Utami; Hery Irwan (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2026)
Transformer oil purification combines electrical isolation, auxiliary power, pressurized oil transfer, dielectric testing, and recommissioning, creating interconnected electrical and oil-handling hazards. This study mapped task-level risks and specified stage-specific controls for the purification workflow at PT PLN Batam using Job Safety Analysis. A single-site case study examined ten stages through observation, 30 maintenance interviews, and operational safety-document review. Hazards were classified retrospectively using a 5 × 5 likelihood–severity matrix. Seven stages were rated high risk and three medium risk. Purification-unit connection received the highest score (15) because electrical and oil-transfer interfaces converge at this stage. Proposed controls emphasize verified isolation, lockout/tagout, competent authorization, pressure-rated connections, containment, spill readiness, and independent restoration checks. Under assumed full implementation and verification, the profile is projected to shift to seven medium-risk and three low-risk stages. The study provides a transparent task-level control map while distinguishing projected residual risk from measured outcomes.